Government sponsored versus private venture capital Canadian evidence - Brander, James A. 1953-; Egan, Edward J.; Hellmann, Thomas (NBER working paper series, 2008)
"This paper investigates the relative performance of enterprises backed by government-sponsored venture capitalists and private venture capitalists. While previous studies focus mainly on investor returns, this paper focuses on a broader set of public policy objectives, including value-creation, innovation, and competition. A number of novel data-collection methods, including web-crawlers, are used to assemble a near-comprehensive data set of Canadian venture-capital backed enterprises. The results indicate that enterprises financed by government-sponsored venture capitalists underperform on a variety of criteria, including value-creation, as measured by the likelihood and size of IPOs and M&As, and innovation, as measured by patents. It is important to understand whether such underperformance arises from a selection effect in which private venture capitalists have a higher quality threshold for investment than subsidized venture capitalists, or whether it arises from a treatment effect in which subsidized venture capitalists crowd out private investment and, in addition, provide less effective mentoring and other value-added skills. We find suggestive evidence that crowding out and less effective treatment are problems associated with government-backed venture capital. While the data does not allow for a definitive welfare analysis, the results cast some doubt on the desirability of certain government interventions in the venture capital market"--National Bureau of Economic Research web site